ACUTE RETINAL NECROSIS AFTER ADMINISTRATION OF ADALIMUMAB, A SYSTEMIC ANTITUMOR NECROSIS FACTOR ANTIBODY. Issue Volume 12:Issues 4(2018) (2018) - Schechet, Sid A.; Garff, Kevin; Klima, Karen; Campbell, Wayne; Schocket, Lisa S.
Abstract : Purpose: To report a case of acute retinal necrosis in a patient on anti–tumor necrosis factor α immunosuppressive therapy. Methods: Case report. Results: A 47-year-old man with psoriasis presented with blurred vision and floaters in the left eye 4 days after receiving his fourth dose of adalimumab, a tumor necrosis factor α antagonist. He was diagnosed with acute retinal necrosis and was treated with intravenous acyclovir as well as prophylactic laser barricade. Seven years later, he is 20/20 with no history of a retinal detachment. Conclusion: Physicians prescribing tumor necrosis factor α antagonist immunosuppressive therapy should be aware of the potential of developing acute retinal necrosis. Abstract : Tumor necrosis factor α antagonists, such as adalimumab, are used to treat inflammatory diseases. These drugs carry an increased risk of infection, but little is known about latent herpetic reactivation or ocular side effects. The authors report a case of unilateral acute retinal necrosis in an adult after adalimumab treatment for psoriasis.